Estudo bibliométrico no Portal Capes: termos e conceitos de educação em museu - Emerich, Adriana Malaman (2017)
Investigates the issue of visibility of scientific journals on the Portal Capes, due to the adoption of keywords in the valuation of an area of knowledge. It aims to reflect on the interference of terms adopted to access the scientific production and the strengthening of the area of knowledge, aiming at a more effective approximation between literature and its users. The study explores the identification of the scientific production focused on the theme "museum education", as a guide in the context of science dissemination (Portal Capes). It was observed that the terminology used for bibliographical productions presents the concepts and terms shared in related areas and of several disciplines, often with contradictory definitions, that do not certify the communication between peers. From this perception, the terms "museology", "interdisciplinary" and "non-formal education", are mainly based on Cerávolo, Japiassú and Trilla. By these references, the terms that were used in the methodological approach were selected, and were identified preferentially in the "Scopes" (section that presents the determined focus on the area of interest of the journals).The data were collected exclusively from Portal Capes, specifically in the area of human knowledge, subarea Education, and in the area of knowledge Applied Social Sciences, sub-area Museology. The research sought to identify in the 1,219 journals of the first subarea and in the 25 journals found in the second, the terminology that was relevant to divulge and access the subject matter. From the results obtained by the bibliometric analysis, which besides the data collection allows a reflection based on the context, it is concluded that "Education in museum" is a theme recognized by both subareas, but little identified by them. Although the term was detected in 9 of the total journals of the subarea Education, and has no occurrence in the subarea Museology, both have shown to be receptive to publish articles on the subject.